The Relationship Between Body Image and Quality of Life in Breast Cancer Patients at H. Adam Malik Center General Hospital Medan City - Dwi Amalia Sari; Siti Zahara Nasution; Zulfendri Zulfendri (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Quality of life and body image is one of the most important outcomes to monitor in breast cancer patients. A better understanding of the quality of life and body image in women with breast cancer can assist in developing and improving therapeutic and treatment interventions in service delivery and care. This study aims to analyze the relationship between body image and quality of life in breast cancer patients. The research design used was a cross-sectional study. The research sampling technique used total sampling. The sample in this study amounted to 105 respondents. The instrument used to measure body image is the BIS (Body Image Scale) and quality of life using the EORTC QLQ BR-45 instrument (The European Organization For Research and Treatment of Cancer Quality of Life Questionnaire). Data analysis in this study used the Spearman statistical test. The results of this study indicate that 65 respondents (61.9%) have a negative body image and 61 respondents (58.1%) have a moderate quality of life. The Spearman Rank test results obtained a correlation coefficient = 0.626 with a significance p-value = 0.000 <0.05 (significance level). Based on this study, it can be concluded that there is a relationship between body image and quality of life in breast cancer patients. It is recommended to room nurses at the H. Adam Malik Medan General Hospital to pay attention to patient feelings by increasing their knowledge of holistic nursing concepts in nursing care and being able to provide information about the patient's condition and condition and provide motivation to breast cancer patients undergoing treatment to patients are more accepting of their body image.Keywords: Body Image, Breast cancer, Quality of life